Evaluation of in silico anticancer activity of bioactive compounds of black ginger as VEGFR2 inhibitors - Em, Pham Canh; Trinh, Tran Trung; Vi, Le Thi Tuong; Ngoc, Vo Thi Bich; Ha, Ly Hong Huong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
The main components of black ginger (Kaempferia parviflora Wall ex Baker.) show diverse biological effects, especially potential anticancer activity. Thirty-five bioactive compounds were screened for anticancer activity by molecular docking with AutoDock Vina software on VEGFR2 kinase. Five bioactive compounds of black ginger showed the strongest interaction with VEGFR2 target, especially stronger than the reference drug Axitinib (-9.2 Kcal/mol) including 5-Hydroxy-7,4'-dimethoxyflavanone (-9.9 Kcal/mol), Kaempferide (-9.7 Kcal/mol), 5-Hydroxy-7-methoxyflavone (-9.6 Kcal/mol), Genkwanin (-9.6 Kcal/mol), and Sakuranetin (-9.5 Kcal/mol). Kaempferide formed the most hydrogen bonds on VEGFR2 kinase with four strong hydrogen bonds (1.76-2.86 Å) and one carbon-hydrogen bond (3.78 Å). The hydrogen bonds are formed at the hydroxy (-OH) and methoxy (-OCH3) groups of these phytocompounds. In particular, these bioactive compounds all demonstrated hydrogen bond formation, hydrogen bond length, and hydrophobic interactions at levels equal to or better than the reference drug Axitinib. Therefore, these compounds could be potential molecules to develop new anticancer drugs on the VEGFR2 target.